Observations of complex frequency comb structure in a harmonically-pumped femtosecond optical parametric oscillator. (18th March 2015) - McCracken, Richard A; Balskus, Karolis; Zhang, Zhaowei; Reid, Derryck T
Abstract: Various schemes allow femtosecond optical parametric oscillators to produce pulses at harmonics of their pump laser repetition frequency, each apparently offering the possibility of generating widely-spaced, tunable frequency combs. Using a 100-MHz Ti:sapphire pump laser, we have compared two alternative optical parametric oscillator architectures, both leading to 300-MHz pulses but one configured in a cavity three times shorter than the pump laser and the other in a cavity one-third longer. Heterodyne measurements between the pump and each of these two systems show that they possess different carrier-envelope offset characteristics, with implications on the coherence and stabilization of the resulting combs.